Preservation of Traditional and Local Foods of Blora Regency as a Gastronomic Tourist Attraction - Arifin Heri Prasetyo; Pradicko Afrindo Saga; Trisagia Mokodongan; Dewi Turgarini (Universitas Pendidikan Indonesia, 2022)
Blora Regency is one of the regencies in Central Java Province which is located in the East. As a Regency, Blora is one of the tourist destinations for both domestic and foreign tourists. Local traditions, nature and culinary are part of tourism activities. This study aims to find out the typical foods of the Blora community, namely Mbah Sakijah’s Kopi Santen, Pak Daman’s Sate Ayam and Pak Pangat’s Lontong Opor Ayam, in terms of the gastronomic component, the efforts made by 9 stakeholders (nona helix) in preserving the eating tradition, and seeing the potential of the nyeruit tradition as gastronomic tourism. The method used in this study uses a qualitative approach or descriptive research. To obtain the necessary data, this research was carried out through in-depth interviews, observation, and documentation so that it requires a process in obtaining and processing the data as a result of research. Blora Regency is the focus of this research. The results of this study indicate the gastronomic components contained in Blora typical food as a gastronomic heritage in Blora Regency. Identification of the role of stakeholders (nona helix) in efforts to preserve Blora typical food and how big the potential for typical foods to be used as gastronomic tourism shows results for developed as gastronomic tourism.